Screening And Education For Prevention Of Cervical Cancer At Kupu Health Center, Tegal District - Anggraeni, Natasha; Destra, Edwin; Jamaludin, Jamaludin; Ulinuha, Ulinuha (Indonesian Scientific Publication, 2023)
Cervical cancer, or what is often referred to as cervical cancer, is one of the most common types of cancer in the gynecological cancer category throughout the world. Education about cervical cancer and the implementation of VIA examinations have a very important role in increasing public awareness of the importance of maintaining cervical health and encouraging early detection of cervical cancer disorders. This outreach activity provides accurate information about cervical cancer, how important it is to maintain cervical health, as well as factors that can influence the risk of developing cervical cancer. In addition, examination using the IVA method makes it possible to carry out an objective evaluation of the condition of each individual's cervix. By increasing public knowledge and understanding of the importance of cervical health, it can encourage the implementation of appropriate preventive measures, such as undergoing regular VIA examinations, avoiding risk factors that can increase the risk of cervical cancer, and supporting early detection efforts. Early detection of cervical cancer through IVA examination allows early identification of cervical disease, so that treatment can be started early to control and slow the progression of the disease. VIA counseling and examination in the context of cervical cancer prevention is a long-term investment in improving people's quality of life and reducing the burden of cervical cancer in society as a whole.